Hydrocracking catalyst containing USY and beta zeolite for hydrocarbon oil and method for hydrocracking hydrocarbon oil using the hydrocracking catalyst

By using USY and β-zeolite compositions that replace the skeleton with titanium and zirconium as catalysts, the problem of low efficiency of hydrocracking catalysts in the prior art is solved, and efficient treatment and quality improvement of heavy hydrocarbon oil is achieved.

CN116096495BActive Publication Date: 2025-02-25SAUDI ARABIAN OIL CO +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080102533.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-28
Filing Date
2020-10-30
Publication Date
2025-02-25
Estimated Expiration
2040-10-30

AI Technical Summary

Technical Problem

Existing hydrocracking catalysts are not efficient when treating heavy hydrocarbon oils, making it difficult to effectively remove pollutants such as sulfur and nitrogen.

Method used

The activity of the catalyst is enhanced by replacing the zeolite skeleton by titanium and zirconium using a catalyst composition including at least one skeleton substituted superstable Y-type zeolite (USY) and beta zeolite.

Benefits of technology

It significantly improves the effectiveness of the hydrocracking process, enhances the treatment capacity of heavy hydrocarbon oil, and improves the quality of hydrocarbon raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004023102940000034
    Figure BDA0004023102940000034
  • Figure BDA0004023102940000141
    Figure BDA0004023102940000141
  • Figure BDA0004023102940000151
    Figure BDA0004023102940000151
Patent Text Reader

Abstract

According to one or more embodiments of the present disclosure, a catalyst composition includes a catalyst support and at least one hydrogenation metal component disposed on the catalyst support. The catalyst support includes at least one USY zeolite having a framework substituted with titanium and zirconium and at least one beta zeolite also having a framework substituted with titanium and zirconium. A method of using such a catalyst in a hydrocracking process is also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. application serial number 16 / 940,635, filed on July 28, 2020, the entire contents of which are incorporated herein by reference. Technical Field

[0003] Embodiments of the present disclosure relate generally to the hydrocracking of hydrocarbon oils, and more particularly to catalyst compositions for the hydrocracking of hydrocarbon oils and methods of using such catalyst compositions. Background Art

[0004] The hydrocracking process is used commercially in a large number of petroleum refineries to process various hydrocarbon feeds with boiling points ranging from 370°C to 520°C in conventional hydrocracking units, and various hydrocarbon feeds with boiling points of 520°C and above in residue hydrocracking units. Generally, the hydrocracking process separates the molecules of the hydrocarbon feed into smaller (i.e., lighter) molecules with higher average volatility and economic value. In addition, the hydrocracking process generally improves the quality of the hydrocarbon feedstock by increasing the hydrogen-to-carbon ratio and by removing organic sulfur and organic nitrogen compounds. The hydrocracking catalyst is a key feature of the hydrocracking process technology.

[0005] Two types of catalysts are used in hydrocracking: pretreatment catalysts and cracking catalysts. Pretreatment catalysts are designed to remove contaminants such as sulfur and nitrogen from heavy hydrocarbon oils. Cracking catalysts are designed to separate low-value heavy molecules into higher-value transportation fuels. Cracking catalysts are typically composed of an active phase metal for hydrogenation, an amorphous support as a binder, and a zeolite as a cracking component. Active phase metals typically include nickel, molybdenum, and tungsten. Exemplary zeolites include ultrastable Y-type zeolites (USY zeolites). Beta zeolite can be added to the catalyst matrix to increase cracking activity and improve low-temperature flow properties. Summary of the invention

[0006] There is a continuing need for more efficient hydrocracking catalyst compositions. It has been discovered that catalyst compositions comprising at least one framework substituted ultrastable Y (hereinafter "USY") zeolite and at least one framework substituted beta zeolite can greatly enhance the effectiveness of the hydrocracking process.

[0007] According to one embodiment, the catalyst composition comprises a catalyst support and at least one hydrogenation metal component disposed on the catalyst support. The catalyst support comprises at least one USY zeolite having a framework substituted with titanium and zirconium and at least one beta zeolite also having a framework substituted with titanium and zirconium.

[0008] According to one embodiment, the method for hydrocracking hydrocarbon oil comprises contacting at least one hydrocarbon oil stream with at least one hydrocracking catalyst composition and hydrogen in a reactor to hydrocracking the hydrocarbon oil stream. The hydrocracking catalyst composition comprises a catalyst support and at least one hydrogenation metal component disposed on the catalyst support. The catalyst support comprises at least one USY zeolite having a framework substituted with titanium and zirconium and at least one beta zeolite also having a framework substituted with titanium and zirconium.

[0009] Additional features and advantages of the embodiments described herein will be set forth in the detailed description which follows, and in part will be apparent to those skilled in the art from the description or may be learned by practicing the described embodiments, including the detailed description and claims provided below. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] The following detailed description of specific embodiments of the present disclosure may be best understood when read in conjunction with the following drawings, in which:

[0011] Figure 1 is a UV-Vis spectrum of unsubstituted β-zeolite and TiZr-β zeolite according to one or more embodiments presently described; and

[0012] Figure 2 is a graph of pore volume versus pore diameter for unsubstituted zeolite beta and TiZr-zeolite beta according to one or more embodiments described herein. DETAILED DESCRIPTION

[0013] In an embodiment, the catalyst composition includes a catalyst support and at least one hydrogenation metal component disposed on the catalyst support. The catalyst support includes at least one USY zeolite having a framework substituted with titanium and zirconium (hereinafter referred to as "TiZr-USY zeolite") and at least one β zeolite also having a framework substituted with titanium and zirconium (hereinafter referred to as "TiZr-β zeolite"). An embodiment of the method will now be described in more detail.

[0014] As used herein, the term "hydrocarbon oil" or "hydrocarbon feedstock" refers to an oily liquid consisting primarily of a mixture of hydrocarbon compounds. Hydrocarbon oils may include refined oils obtained from crude oil, synthetic crude oil, asphalt, oil sands, shale oil or kerosene. The term "refined oil" includes, but is not limited to, vacuum gas oil (VGO), deasphalted oil (DAO) obtained from a solvent deasphalting process, demetallized oil (DMO), light and / or heavy coker gas oils obtained from a coking process, cycle oils obtained from a fluidized catalytic cracking (FCC) process, and gas oils obtained from a visbreaking process.

[0015] As used herein, the term "hydrocarbon" refers to a chemical compound composed entirely of carbon and hydrogen atoms.

[0016] As used herein, the term "lattice constant" refers to the physical size of a unit cell in a crystal lattice. The lattice constant can be determined by ASTM D3942-03 entitled "Standard Test Method for Determining Unit Cell Size of Faujasite-Type Zeolites", the entire contents of which are incorporated herein by reference. Beta zeolite has a tetragonal system. Crystals with a tetragonal system have three mutually perpendicular axes, two of which are of equal length. The crystal structure can be defined according to its simplest repeating unit (unit cell), which is defined by three translations a, b and c and three angles α, β and γ. It is usually convenient to refer to the lattice planes that pass through the lattice points (the same point in space) in the structure. The reciprocals of the intercepts of these lattice planes on the three axes (x, y, z) are called Miller indices (h, k, l), and describe the three-dimensional lattice planes. The spacing between adjacent lattice planes, which is particularly relevant in the description of diffraction, is designated as dhkl. For the tetragonal system, the lattice parameters include:

[0017] a=b≠c

[0018] α=β=γ=90°

[0019] Among them, a is The h in the figure is related to the unit cell size, and b is related to The unit cell size is related to k in , and c is related to The lattice constant of zeolite beta is determined based on the tetragonal unit cell using the following equation:

[0020]

[0021] wherein a, b, c, h, k and l are as defined above, and d is The interplanar spacing unique to a given plane of units.

[0022] As used herein, the term "specific surface area" refers to the total surface area of ​​a zeolite or catalyst per unit mass. The specific surface area can be determined by ASTM D3663-03, entitled "Standard Test Method for Surface Area of ​​Catalysts and Catalyst Supports," the entire contents of which are incorporated herein by reference. Alternatively, the Brunauer-Emmett-Teller ("BET") model can be used to determine the specific surface area. Alternatively, the specific surface area can be determined by ASTM D4365-19, entitled "Standard Test Method for Determining Catalyst Micropore Volume and Zeolite Area," the entire contents of which are incorporated herein by reference.

[0023] As used herein, the term "hydrogen / oil ratio" or "hydrogen to oil ratio" refers to a standard measure of the volumetric rate of hydrogen circulating through a reactor relative to the volume of feed. The hydrogen / oil ratio can be determined by comparing the flow rate of the hydrogen stream to the flow rate of the hydrocarbon feed using a standard flow meter.

[0024] As used herein, the term "liquid hourly space velocity" or "LHSV" refers to the ratio of the liquid flow rate of the hydrocarbon feed to the volume or mass of the catalyst.

[0025] In one aspect, the catalyst composition may include a catalyst support and at least one hydrogenation metal component. In an embodiment, the catalyst composition may include a support of 60wt.% to 99.99wt.%. For example, the catalyst composition may include a support of 65wt.% to 95wt.%, 60wt.% to 90wt.%, 65wt.% to 85wt.%, or even 70wt.% to 80wt.%. It should be understood that the catalyst composition may include a support in an amount in a range formed from any lower limit of such a range as described herein to any upper limit of such a range as described herein. In an embodiment, the catalyst composition may include a hydrogenation metal component of 0.01wt.% to 40wt.%. For example, the catalyst composition may include a hydrogenation metal component of 1wt.% to 40wt.%, 5wt.% to 35wt.%, 10wt.% to 30wt.%, or even 15wt.% to 25wt.%. It should be understood that the catalyst composition may include a hydrogenation metal component in an amount in a range formed from any lower limit of such a range as described herein to any upper limit of such a range as described herein. Without being bound by any particular theory, it is believed that when the amount of hydrogenation component in the catalyst composition is too large relative to the amount of support, the dispersion of the hydrogenation metal on the catalyst is not optimal. For example, when the catalyst composition includes more than 40 wt.% of the hydrogenation component, the hydrogenation metal may agglomerate on the support.

[0026] The catalyst support may include at least one USY zeolite and at least one beta zeolite. Each type of zeolite may have a framework substituted with titanium and zirconium. In an embodiment, the framework substitution may be achieved by a post-modification process, in which the zeolite is dealuminated and then a transition metal, such as Ti and / or Zr, is inserted. Therefore, relative to unsubstituted zeolites, zeolites whose frameworks are replaced with titanium and zirconium may have a greater silicon-aluminum ratio (hereinafter referred to as "SAR"). Without being bound by any particular theory, it is believed that this post-modification produces mesopores, which enable zeolites to have the ability to accept macromolecules in the pores. As used herein, the term "mesoporosity" refers to that a zeolite contains a plurality of pores having a diameter of 2nm to 50nm. In addition, it is believed that the mesopores increase the number of medium-strength acid sites, while reducing the number of strong acid sites, and enhance the dispersion of hydrogenation metals on the catalyst surface.

[0027] In an embodiment, the post-modification of USY or beta zeolite can be completed by the following process. The zeolite can be placed in a suspension in a liquid so that the mass ratio of the liquid to the solid zeolite is 5 to 15. An inorganic acid or an organic acid can be added to the suspension so that the pH of the suspension is less than 2. At least one zirconium compound and at least one titanium compound are added to the acidic suspension, which are then mixed and neutralized to obtain a post-modified catalyst. An exemplary method for preparing a titanium and zirconium-substituted USY zeolite framework is described in U.S. Patent No. 10,293,332, the entire contents of which are incorporated herein by reference. An exemplary method for preparing a titanium and zirconium-substituted beta zeolite framework is described in U.S. Serial No. 16 / 589,719 filed on October 1, 2019, the entire contents of which are incorporated herein by reference.

[0028] Framework substitution can be monitored, for example, by ultraviolet, visible and near infrared spectrophotometry (UV-Vis-NIR or UV-Vis), Fourier transform infrared spectroscopy (FT-IR) or nuclear magnetic resonance spectroscopy (NMR). For example, zirconium atoms are known to produce characteristic effects in the UV-Vis spectrum of TiZr-β zeolite in the range of about 200 nm to about 220 nm.

[0029] In an embodiment, the USY zeolite and the beta zeolite may be independently substituted with 0.1 wt.% to 5 wt.% zirconium and 0.1 wt.% to 5 wt.% titanium, in both cases calculated on an oxide basis. For example, the USY zeolite and the beta zeolite may be independently substituted with 0.5 wt.% to 4.5 wt.% zirconium and 0.5 wt.% to 4.5 wt.% titanium, 1 wt.% to 4 wt.% zirconium and 1 wt.% to 4 wt.% titanium, 1.5 wt.% to 3.5 wt.% zirconium and 1.5 wt.% to 3.5 wt.% titanium, or even 2 wt.% to 3 wt.% zirconium and 2 wt.% to 3 wt.% titanium. It should be understood that any amount of zirconium substitution described herein may be used in combination with any amount of titanium substitution described herein. In addition, it should be understood that the range of zirconium or titanium substitution may be formed by any lower limit of such substitution described herein and any upper limit of such substitution described herein.

[0030] Without being bound by any particular theory, it is believed that adding zirconium compounds and / or titanium compounds in an amount less than 0.1 wt.% does not improve the solid acid properties of the zeolite. In contrast, adding zirconium compounds and / or titanium compounds in an amount exceeding 5 wt.% does not further improve the zeolite activity and may result in an unnecessary increase in the cost of the resulting catalyst.

[0031] In some embodiments, the TiZr-USY zeolite may have a lattice constant of 2.43nm to 2.45nm. For example, the lattice constant of the TiZr-USY zeolite may be 2.431nm to 2.449nm, 2.432nm to 2.448nm, 2.433nm to 2.447nm, 2.434nm to 2.446nm, 2.435nm to 2.445nm, 2.436nm to 2.444nm, 2.437nm to 2.443nm, 2.438nm to 2.442nm, or even 2.439nm to 2.441nm. It should be understood that the lattice constant of the TiZr-USY zeolite may be within a range formed from any lower limit of such lattice constant described herein to any upper limit of such lattice constant described herein. The lattice constant of the TiZr-β zeolite may be a=1.26nm to 1.27nm, b=1.26nm to 1.27nm, and c=26.2nm to 26.5nm, or a=1.263nm to 1.267nm, b=1.263nm to 1.263nm, and c=26.3nm to 26.4nm. It should be understood that the lattice constant of the TiZr-β zeolite may be within a range formed from any lower limit of such lattice constant described herein to any upper limit of such lattice constant described herein.

[0032] Without being bound by any particular theory, it is believed that the lattice constant of the TiZr-USY zeolite is less than 2.43 nm, which may result in a reduction in the activity of the hydrocracking catalyst ultimately formed. This reduction is believed to be a result of the high SiO2 / Al2O3 molar ratio and a small amount of solid acid sites in the zeolite framework structure as active sites for hydrocarbon decomposition. On the contrary, due to the low heat resistance of the TiZr-USY zeolite, the lattice constant of the TiZr-USY zeolite exceeds 2.45 nm, which may result in the rupture of the crystal structure of the TiZr-USY zeolite during the hydrocracking reaction. The rupture of the crystal structure of the TiZr-USY zeolite may result in a reduction in the activity of the hydrocracking catalyst composition ultimately formed. Without being bound by any particular theory, it is believed that similar effects can be observed above the maximum lattice constant of the above-mentioned TiZr-β zeolite and below the minimum lattice constant of the above-mentioned TiZr-β zeolite.

[0033] In an embodiment, the TiZr-USY zeolite may have a diameter of 600 m 2 / g to 900m 2 For example, the specific surface area of ​​the TiZr-USY zeolite can be 610 m 2 / g to 890m 2 / g, 620m 2 / g to 880m 2 / g, 630m2 / g to 870m 2 / g, 640m 2 / g to 860m 2 / g, 650m 2 / g to 850m 2 / g, 660m 2 / g to 840m 2 / g, 670m 2 / gg to 830m 2 / g, 680m 2 / g to 820m 2 / g, 690m 2 / g to 810m 2 / g、700m 2 / g to 800m 2 / g, 710m 2 / g to 790m 2 / g, 720m 2 / g to 780m 2 / g, 730m 2 / g to 770m 2 / g, or even 740m 2 / g to 760m 2 / g. It should be understood that the specific surface area of ​​the TiZr-USY zeolite may be within a range formed from any lower limit of such specific surface area described herein to any upper limit of such specific surface area described herein. The TiZr-β zeolite may have a specific surface area of ​​400 m 2 / g to 800m 2 For example, the specific surface area of ​​the TiZr-β zeolite can be 410 m 2 / g to 790m 2 / g, 420m 2 / g to 780m 2 / g, 430m 2 / g to 770m 2 / g, 440m 2 / g to 760m 2 / g, 450m 2 / g to 750m 2 / g, 460m 2 / g to 740m 2 / g, 470m 2 / g to 730m 2 / g, 480m 2 / g to 720m2 / g, 490m 2 / g to 710m 2 / g、500m 2 / g to 700m2 / g, 510m 2 / g to 690m 2 / g, 520m 2 / g to 680m 2 / g, 530m 2 / g to 670m 2 / g, 540m 2 / g to 660m 2 / g, 550m 2 / g to 650m 2 / g, 560m 2 / g to 640m 2 / g, 570m 2 / g to 630m 2 / g,580m 2 / g to 620m 2 / g, or even 590m 2 / g to 610m 2 It should be understood that the specific surface area of ​​the TiZr-β zeolite can be within a range formed from any lower limit of such specific surface area described herein to any upper limit of such specific surface area described herein.

[0034] Without being bound by any particular theory, it is believed that the specific surface area of ​​the TiZr-USY zeolite is less than 600 m 2 / g and / or the specific surface area of ​​the TiZr-β zeolite is less than 200 Å, which may result in a reduction in the number of available solid acid sites, thereby reducing the catalyst activity of the resulting hydrocracking catalyst composition to an unsatisfactory level.

[0035] In an embodiment, the catalyst composition including the TiZr-USY zeolite and the TiZr-β zeolite may have a 2 / g to 450m 2 For example, the specific surface area of ​​the catalyst composition including the TiZr-USY zeolite and the TiZr-β zeolite may be 210 m 2 / g to 440m 2 / g, 220m 2 / g to 430m 2 / g, 230m 2 / g to 420m 2 / g, 240m 2 / g to 410m 2 / g, 250m 2 / g to 400m 2 / g, 260m 2 / g to 390m 2 / g, 270m2 / g to 380m 2 / g, 280m 2 / g to 370m 2 / g, 290m 2 / g to 360m 2 / g、300m 2 / g to 350m 2 / g, 310m 2 / g to 340m 2 / g or even 320m 2 / g to 330m 2 / g. It should be understood that the specific surface area of ​​the catalyst composition including the TiZr-USY zeolite and the TiZr-β zeolite can be within a range formed from any lower limit of such specific surface area described herein to any upper limit of such specific surface area described herein. Without being bound by any particular theory, it is believed that when the specific surface area is less than 200 m 2 / g, the hydrocracking rate decreases and the yield of the middle distillate decreases. However, if the specific surface area exceeds 450m 2 / g, the hydrocracking rate may become too high and the product selectivity may be adversely altered.

[0036] In an embodiment, the TiZr-USY zeolite may have a molar ratio of SiO2 to Al2O3 of 10 to 100. For example, the TiZr-USY zeolite may have a molar ratio of SiO2 to Al2O3 of 11 to 99, 12 to 98, 13 to 97, 14 to 96, 15 to 95, 16 to 94, 17 to 93, 18 to 92, 19 to 91, 20 to 90, 21 to 89, 22 to 88, 23 to 87, 24 to 86, 25 to 85, 26 to 84, 27 to 83, 28 to 82, 29 to 81, 30 to 80, 31 to 79, 32 to 78, 33 to 79, 34 to 79, 35 to 79, 36 to 79, 37 to 79, 38 to 79, 39 to 80, 40 to 81, 41 to 82, 42 to 83, 43 to 84, 44 to 85 , 33 to 77, 34 to 76, 35 to 75, 36 to 74, 37 to 73, 38 to 72, 39 to 71, 40 to 70, 41 to 69, 42 to 68, 43 to 67, 44 to 66, 45 to 65, 46 to 64, 47 to 63, 48 to 62, 49 to 61, 50 to 60, 51 to 59, 52 to 58, 53 to 57, or even 54 to 56. It should be understood that the ratio of SiO2 to Al2O3 of the TiZr-USY zeolite can be within a range formed from any lower limit of such ratio described herein to any upper limit of such ratio described herein.

[0037] In an embodiment, the TiZr-beta zeolite may have a molar ratio of SiO2 to Al2O3 of 10 to 200. For example, the TiZr-beta zeolite may have a molar ratio of SiO2 to Al2O3 of 15 to 195, 20 to 190, 25 to 185, 20 to 180, 25 to 175, 30 to 170, 35 to 165, 40 to 160, 45 to 155, 50 to 150, 55 to 145, 60 to 140, 65 to 135, 70 to 130, 75 to 125, 80 to 120, 85 to 115, 90 to 110, or even 95 to 105. It should be understood that the ratio of SiO2 to Al2O3 of the TiZr-beta zeolite may be within a range formed from any lower limit of such ratio described herein to any upper limit of such ratio described herein.

[0038] In an embodiment, the catalyst composition including the TiZr-USY zeolite and the TiZr-β zeolite may include a plurality of or smaller holes. These diameters are The volume of the pores or smaller is 0.4 mL / g to 0.75 mL / g. For example, the pore volume can be 0.41 mL / g to 0.74 mL / g, 0.42 mL / g to 0.73 mL / g, 0.43 mL / g to 0.72 mL / g, 0.44 mL / g to 0.71 mL / g, 0.45 mL / g to 0.7 mL / g, 0.46 mL / g to 0.69 mL / g, 0.47 mL / g to 0.68 mL / g, 0.48 mL / g to 0.67 mL / g, 0.49 mL / g to 0.69 mL / g, 0.50 mL / g to 0.69 mL / g, 0.51 mL / g to 0.69 mL / g, 0.52 mL / g to 0.69 mL / g, 0.53 mL / g to 0.69 mL / g, 0.54 mL / g to 0.69 mL / g, 0.56 mL / g to 0.69 mL / g, 0.57 mL / g to 0.69 mL / g, 0.58 mL / g to 0.69 mL / g, 0.59 mL / g to 0.69 mL / g, 0.61 mL / g to 0.61 mL / g, 0.62 mL / g to 0.63 mL / g, 0.64 mL / g to 0.65 mL / g, 0.66 mL / g to 0.67 mL / g, 0.67 mL / g to 0.67 mL / g, 0.68 mL / g to 0.69 mL / g, 0.69 mL / g to 0.69 mL / g, 0.61 mL / g to 0.69 mL / g, 0.62 mL / g g to 0.66 mL / g, 0.5 mL / g to 0.65 mL / g, 0.51 mL / g to 0.64 mL / g, 0.52 mL / g to 0.63 mL / g, 0.53 mL / g to 0.62 mL / g, 0.54 mL / g to 0.61 mL / g, 0.55 mL / g to 0.6 mL / g, 0.56 mL / g to 0.59 mL / g, or even 0.57 mL / g to 0.58 mL / g. It should be understood that the range of diameters including The pore volume of the pores of the catalyst composition of the TiZr-USY zeolite and the TiZr-β zeolite of 100 Å or less may be within a range formed from any lower limit of such pore volume described herein to any upper limit of such pore volume described herein.

[0039] Without being bound by any particular theory, it is believed that if the pore volume is less than 0.40 mL / g, the specific surface area is reduced. As a result, the hydrocracking catalyst activity and the yield of the middle distillate are reduced. On the contrary, if the pore volume exceeds 0.75 mL / g, the specific surface area is increased. As a result, the hydrocracking rate and product selectivity may be adversely changed.

[0040] In an embodiment, the carrier may include 70 wt.% to 99 wt.% TiZr-USY zeolite and 1 wt.% to 30 wt.% TiZr-β zeolite, based on the total zeolite content of the carrier. For example, the carrier may include 71 wt.% to 98 wt.%, 72 wt.% to 97 wt.%, 73 wt.% to 96 wt.%, 74 wt.% to 95 wt.%, 75 wt.% to 94 wt.%, 76 wt.% to 93 wt.%, 77 wt.% to 92 wt.%, 78 wt.% to 91 wt.%, 79 wt.% to 90 wt.%, 80 wt.% to 89 wt.%, 81 wt.% to 88 wt.%, 82 wt.% to 87 wt.%, 83 wt.% to 86 wt.%, or even 84 wt.% to 85 wt.% TiZr-USY zeolite. For further examples, the support can include 2 wt.% to 29 wt.%, 3 wt.% to 28 wt.%, 4 wt.% to 27 wt.%, 5 wt.% to 26 wt.%, 6 wt.% to 25 wt.%, 7 wt.% to 24 wt.%, 8 wt.% to 23 wt.%, 9 wt.% to 22 wt.%, 10 wt.% to 21 wt.%, 11 wt.% to 20 wt.%, 12 wt.% to 19 wt.%, 13 wt.% to 18 wt.%, 14 wt.% to 17 wt.%, or even 15 wt.% to 16 wt.% of TiZr-β zeolite. It should be understood that any amount of TiZr-USY zeolite described herein can be used in combination with any amount of TiZr-β zeolite described herein. Furthermore, it should be understood that ranges of TiZr-USY zeolite or TiZr-Beta zeolite can be formed by any lower limit of such zeolite content described herein and any upper limit of such zeolite content described herein.

[0041] In an embodiment, the hydrogenation metal component may include one or more metals of Group 6 and Groups 8-11 of the Periodic Table of Elements, as numbered by the International Union of Pure and Applied Chemistry in April 2020. For example, the hydrogenation metal component may include one or more of chromium, molybdenum, tungsten, iron, cobalt, nickel, copper, ruthenium, rhodium, palladium, silver, osmium, iridium, platinum, and gold.

[0042] In an embodiment, the catalyst composition may include other additives. For example, in addition to the above-mentioned zeolite, the catalyst composition may also include one or more inorganic oxides. The inorganic oxide may be used as a granulating agent or a binder. Exemplary inorganic oxides include, but are not limited to, aluminum oxide, silicon dioxide, titanium dioxide, silicon dioxide-alumina, aluminum oxide-titania, aluminum oxide-zirconia, aluminum oxide-boria, phosphorus-alumina, silicon dioxide-alumina-boria, phosphorus-alumina-boria, phosphorus-alumina-silicon dioxide, silicon dioxide-alumina-titania and silicon dioxide-alumina-zirconia.

[0043] In an embodiment, the one or more inorganic oxides may include components of the carrier. In an embodiment, the framework-substituted zeolite present may account for 1wt.% to 80wt.%, 10wt.% to 75wt.%, 20wt.% to 70wt.%, or even 30wt.% to 60wt.% of the carrier. In an embodiment, the inorganic oxide content may be 98wt.% to 20wt.%, 90wt.% to 25wt.%, 80wt.% to 30wt.% or even 70wt.% to 40wt.% of the carrier. It should be understood that the framework-substituted zeolite may exist in a range formed from any lower limit of such concentration described herein to any upper limit of such concentration described herein. It should also be understood that the inorganic oxide may exist in a range formed from any lower limit of such concentration described herein to any upper limit of such concentration described herein. Without being bound by any particular theory, it is believed that if the amount of binder is less than 20wt.%, the mechanical strength of the catalyst may be reduced, and if the zeolite content is less than 2wt.%, the cracking ability of the catalyst may be reduced.

[0044] On the other hand, the method for hydrocracking hydrocarbon oil comprises contacting at least one hydrocarbon oil stream with at least one hydrocracking catalyst composition and hydrogen in a reactor to hydrocracking the hydrocarbon oil stream. The hydrocracking catalyst may be as described above. That is, the hydrocracking catalyst may include a catalyst support and at least one hydrogenation metal component disposed on the catalyst support. The catalyst support may include at least one TiZr-USY zeolite and at least one TiZr-β zeolite.

[0045] The reactor may be operated in a temperature range of 300° C. to 500° C. For example, the reactor may be operated in a temperature range of 310° C. to 490° C., 320° C. to 480° C., 330° C. to 470° C., 340° C. to 460° C., 350° C. to 450° C., 360° C. to 440° C., 370° C. to 430° C., 380° C. to 420° C., 390° C. to 410° C., or even 395° C. to 405° C. It should be understood that the reactor may be operated in a temperature range formed by any lower limit of such temperature described herein and any upper limit of such temperature described herein.

[0046] The boiling point of the hydrocarbon oil may be 375° C. to 833° C. For example, the boiling point of the hydrocarbon oil may be 400° C. to 800° C., 450° C. to 750° C., 500° C. to 700° C., 550° C. to 650° C., or even 575° C. to 625° C. It should be understood that the boiling point of the hydrocarbon oil may be within a temperature range formed by any lower limit of such temperature described herein and any upper limit of such temperature described herein.

[0047] Hydrogen can be used to produce saturated hydrocarbons in the hydrocracking process. The hydrogen can be added to the reactor at a pressure of 3.5 MPa to 35 MPa. For example, the hydrogen can be added to the reactor at a pressure of 4 MPa to 34.5 MPa, 4.5 MPa to 34 MPa, 5 MPa to 33.5 MPa, 5.5 MPa to 33 MPa, 6 MPa to 32.5 MPa, 6.5 MPa to 32 MPa, 7 MPa to 31.5 MPa, 7.5 MPa to 31 MPa, 8 MPa to 30.5 MPa, 8.5 MPa to 30 MPa, 9 MPa to 29.5 MPa, 9.5 MPa to 29 MPa, 10 MPa to 28.5 MPa, 10.5 MPa to 28 MPa, 11 MPa to 27.5 MPa, 11.5 MPa to 27 MPa, 12 MPa to 26.5MPa, 12.5MPa to 26MPa, 13MPa to 25.5MPa, 13.5MPa to 25MPa, 14MPa to 24.5MPa, 14.5MPa to 24MPa, 15MPa to 23.5MPa, 15.5MPa to 23MPa, 16MPa to 22.5MPa, 16.5MPa to 22MPa, 17MPa to 21.5MPa, 17.5MPa to 21MPa, 18MPa to 20.5MPa, 18.5MPa to 20MPa, or even 19MPa to 19.5MPa. It should be understood that the hydrogen can be added to the reactor within a pressure range from any lower limit of this pressure as described herein to any upper limit of this pressure as described herein. Without being bound by any particular theory, it is believed that at lower hydrogen pressures, process performance will be significantly reduced. In contrast, processes using high hydrogen pressures are believed to require specialized equipment which may significantly increase the cost of the process.

[0048] The hydrogen feed and hydrocarbon oil feed can be adjusted so that the hydrogen / oil ratio in the reactor can be 500 normal cubic meters per cubic meter (hereinafter referred to as "Nm 3 / m 3 ”) to 2500Nm 3 / m 3 , where the standard cubic meter is defined as the volume in cubic meters at standard temperature and pressure (0°C and 0.1 MPa). For example, the hydrogen / oil ratio may be 550 Nm 3 / m 3 Up to 2450Nm 3 / m 3 、600Nm 3 / m 3 Up to 2400Nm 3 / m 3 、650Nm 3 / m 3Up to 2350Nm 3 / m 3 、700Nm 3 / m 3 Up to 2300Nm 3 / m 3 、750Nm 3 / m 3 Up to 2250Nm 3 / m 3 、800Nm 3 / m 3 Up to 2200Nm 3 / m 3 、850Nm 3 / m 3 Up to 2150Nm 3 / m 3 、900Nm 3 / m 3 Up to 2100Nm 3 / m 3 、950Nm 3 / m 3 Up to 2050Nm 3 / m 3 、1000Nm 3 / m 3 Up to 2000Nm 3 / m 3 、1050Nm 3 / m 3 to 1950Nm3 / m3, 1100Nm3 / m3 to 1900Nm 3 / m 3 、1150Nm 3 / m 3 Up to 1850Nm 3 / m 3 、1200Nm 3 / m 3 Up to 1800Nm 3 / m 3 、1250Nm 3 / m 3 Up to 1750Nm 3 / m 3 、1300Nm 3 / m 3 Up to 1700Nm 3 / m 3 、1250Nm 3 / m 3 Up to 1650Nm 3 / m 3 、1300Nm 3 / m 3Up to 1500Nm 3 / m 3 Or even 1350Nm 3 / m 3 Up to 1450Nm 3 / m 3 It should be understood that the hydrogen / oil ratio can be within a ratio range from any lower limit of such ratios described herein to any upper limit of such ratios described herein. Without being bound by any particular theory, it is believed that at lower hydrogen / oil ratios, process performance will be significantly reduced. Conversely, it is believed that processes using high hydrogen / oil ratios require specialized equipment, which may significantly increase process costs and may increase gas holdup in the system, thereby reducing process performance.

[0049] The liquid hourly space velocity (hereinafter referred to as "LHSV") of the hydrocarbon feed in the reactor can be from 0.1 / hour to 10 / hour. For example, the liquid hourly space velocity can be from 0.5 / hour to 9.5 / hour, 1 / hour to 9 / hour, 1.5 / hour to 8.5 / hour, 2 / hour to 8 / hour, 2.5 / hour to 7.5 / hour, 3 / hour to 7 / hour, 3.5 / hour to 6.5 / hour, 4 / hour to 6 / hour, or even 4.5 / hour to 5.5 / hour. It should be understood that the LHSV can be within a range formed from any lower limit of the LHSV described herein to any upper limit of the LHSV described herein.

[0050] As described above, the hydrocracking process can be carried out in one or more reactors. Flow reactors are well suited for this method, although the subject matter described herein is not limited thereto. Exemplary flow reactors include, but are not limited to, stirred tank reactors, ebullating bed reactors, baffled slurry tanks, fixed bed reactors, rotating tubular reactors, slurry bed reactors, and combinations of two or more thereof.

[0051] According to one aspect, alone or in combination with any other aspect, the catalyst composition comprises a catalyst support and at least one hydrogenation metal component disposed on the catalyst support. The catalyst support comprises at least one USY zeolite having a framework substituted with titanium and zirconium (TiZr-USY zeolite) and at least one β zeolite also having a framework substituted with titanium and zirconium (TiZr-β zeolite).

[0052] According to a second aspect, alone or in combination with any other aspect, the at least one TiZr-USY zeolite and the at least one TiZr-β zeolite are each independently substituted with 0.1 to 5 wt.% zirconium atoms and 0.1 to 5 wt.% titanium calculated on an oxide basis.

[0053] According to a third aspect, alone or in combination with any other aspect, the at least one hydrogenation metal component is selected from chromium, molybdenum, tungsten, iron, cobalt, nickel, copper, ruthenium, rhodium, palladium, silver, osmium, iridium, platinum, gold, and combinations of two or more thereof.

[0054] According to a fourth aspect, alone or in combination with any other aspect, the at least one TiZr-USY zeolite comprises a lattice constant of 2.43 nm to 2.45 nm.

[0055] According to a fifth aspect, alone or in combination with any other aspect, the at least one TiZr-USY zeolite comprises 600 m 2 / g to 900m 2 / g specific surface area.

[0056] According to a sixth aspect, alone or in combination with any other aspect, the catalyst composition comprising the at least one TiZr-USY zeolite and the at least one TiZr-β zeolite comprises 200 m 2 / g to 450m 2 / g specific surface area.

[0057] According to a seventh aspect, alone or in combination with any other aspect, the at least one TiZr-USY zeolite comprises a molar ratio of SiO2 to Al2O3 of 10 to 100.

[0058] According to an eighth aspect, alone or in combination with any other aspect, the catalyst composition comprising the at least one TiZr-USY zeolite and the at least one TiZr-β zeolite comprises a plurality of Or smaller pores, the pore volume is 0.4mL / g to 0.75mL / g.

[0059] According to a ninth aspect, alone or in combination with any other aspect, the at least one hydrogenation metal component comprises 0.01 wt.% to 40 wt.% of the catalyst composition.

[0060] According to a tenth aspect, alone or in combination with any other aspect, the at least one TiZr-beta zeolite comprises lattice constants of a = 1.26 nm to 1.27 nm, b = 1.26 nm to 1.27 nm, and c = 26.2 nm to 26.5 nm.

[0061] According to an eleventh aspect, alone or in combination with any other aspect, the at least one TiZr-β zeolite comprises 400 m 2 / g to 800m 2 / g specific surface area.

[0062] According to a twelfth aspect, alone or in combination with any other aspect, the at least one TiZr-beta zeolite comprises a molar ratio of SiO2 to Al2O3 of 10 to 200.

[0063] According to a thirteenth aspect, alone or in combination with any other aspect, the catalyst support comprises 70 wt.% to 99 wt.% TiZr-USY zeolite, based on the total zeolite content of the support.

[0064] According to a fourteenth aspect, alone or in combination with any other aspect, the catalyst support comprises 1 wt.% to 30 wt.% TiZr-beta zeolite based on the total zeolite content of the support.

[0065] According to a fifteenth aspect, alone or in combination with any other aspect, the catalyst support comprises 1 wt.% to 80 wt.% total TiZr-USY zeolite and TiZr-β zeolite.

[0066] According to a sixteenth aspect, alone or in combination with any other aspect, a method for hydrocracking a hydrocarbon oil comprises contacting at least one hydrocarbon oil stream with at least one hydrocracking catalyst composition and hydrogen in a reactor to hydrocracking the hydrocarbon oil stream. The hydrocracking catalyst composition comprises a catalyst support and at least one hydrogenation metal component disposed on the catalyst support. The catalyst support comprises at least one TiZr-USY zeolite and at least one TiZr-β zeolite.

[0067] According to a seventeenth aspect, alone or in combination with any other aspect, the reactor is operated at a temperature of 300°C to 500°C.

[0068] According to an eighteenth aspect, alone or in combination with any other aspect, the hydrocarbon oil has a boiling point of 375°C to 833°C.

[0069] According to a nineteenth aspect, alone or in combination with any other aspect, the hydrogen is added to the reactor at a pressure of 3.5 MPa to 35 MPa.

[0070] According to the twentieth aspect, alone or in combination with any other aspect, the reactor has a mass of 500 Nm 3 / m 3 Up to 2500Nm 3 / m 3 of hydrogen / oil ratio.

[0071] According to the twenty-first aspect, alone or in combination with any other aspect, the reactor has a liquid hourly space velocity of 0.1 / hour to 10 / hour.

[0072] According to the twenty-second aspect, alone or in combination with any other aspect, the reactor includes a flow reactor selected from: a stirred tank reactor, a boiling bed reactor, a baffled slurry tank, a fixed bed reactor, a rotating tubular reactor, a slurry bed reactor and a combination of two or more thereof.

[0073] Example

[0074] Using the above-described embodiments, exemplary catalyst compositions were prepared and characterized as follows.

[0075] Synthesis and Characterization of Framework-Substituted Zeolites

[0076] TiZr-USY zeolite was prepared as described in US Pat. No. 10,293,332, the entire contents of which are incorporated herein by reference.

[0077] TiZr-β zeolite was prepared as described in U.S. Serial No. 16 / 589,719 filed on October 1, 2019, the entire contents of which are incorporated herein by reference. Briefly, β zeolite was acid treated with sulfuric acid at 40°C. Titanium sulfate and zirconium sulfate were added to the acid-suspended β zeolite to obtain 1 wt.% TiO2 and 1 wt.% ZrO2, respectively. After stirring for 4 hours, the resulting material was washed with water at 60°C to remove residual sulfate. UV-Vis analysis was performed using JASCO V-679 to characterize the TiZr-β zeolite. As Figure 1 Titanium was successfully inserted into the framework of zeolite β, as indicated by the peak at about 200 nm relative to the unsubstituted zeolite β. In addition, TiZr-zeolite β exhibited mesoporosity after acid treatment, as shown in Figure 2 This is shown by the peak pore size in the 10 nm region, which is not present in unsubstituted zeolite beta.

[0078] TiZr-β zeolite was analyzed to determine its specific surface area (SA) and silicon to aluminum ratio (SAR), and the concentrations of TiO2 and ZrO2 present were determined. The SA and SAR of unsubstituted β zeolite were also determined. SA can be determined as described above. Quantitative composition analysis was determined by X-ray fluorescence spectroscopy (XRF), and the SAR based on moles was derived from the XRF data. The results of these analyses are listed in Table 1.

[0079] Table 1

[0080]

[0081] 1 N / P = Not present

[0082] Preparation of catalyst composition

[0083] Catalyst composition 1 was formulated using 5 wt.% TiZr-β zeolite, 25 wt.% TiZr-USY zeolite, and 70 wt.% pure alumina binder. Catalyst composition 2 was formulated using 30 wt.% TiZr-USY zeolite and 70 wt.% pure alumina binder. The combined TiZr-USY zeolite and binder are referred to as "supports". For the purpose of specifying the component concentrations of the catalyst composition, the hydrogenation component (which includes nickel and molybdenum for both catalyst composition 1 and catalyst composition 2) is calculated as a component of the support. The hydrogenation component is added to the support concentration to obtain a concentration relative to the final catalyst composition (support + metal). For example, a catalyst composition containing 100 kg of support and 32 kg of hydrogenation component will have a hydrogenation component of 24 wt.% of the total catalyst composition.

[0084] Table 2 provides the composition analysis of catalyst composition 1 and catalyst composition 2. The specific surface area and pore volume are determined as follows. 0.02 g to 0.05 g of sample (zeolite or catalyst composition) is degassed at room temperature for 5 hours using an adsorption measurement device (e.g., a fully automatic gas adsorption device "AUTOSORB-1" manufactured by Quanta Instruments). The adsorption-desorption isotherm is measured at liquid nitrogen temperature to calculate the specific surface area per unit mass using the BET equation of the multi-point method. In addition, the pore distribution and pore volume (pore size: or less). The compacted bulk density can be determined as follows. The sample is precalcined at 500°C for 1 hour. The sample is then cooled in a desiccator. 100 g of the dry sample is loaded into a cylinder and compacted. Based on the volume of the sample, the compacted bulk density is calculated as the weight of the sample divided by its volume.

[0085] Table 2

[0086]

[0087] Pilot hydrocracking process

[0088] Both catalyst composition 1 and catalyst composition 2 were used in a hydrocracking process using vacuum gas oil (VGO) feed. The density of VGO is 0.923 g / cm 3 %, a sulfur content of 2.51 wt.%, and a nitrogen content of 960 ppm. The naphtha fraction is considered to be the fraction from the C5 cut point (i.e. about 32°C) to 145°C. The kerosene fraction is considered to be the fraction from 145°C to 260°C. The gas oil fraction is considered to be the fraction from 260°C to 360°C. The middle distillate fraction is considered to be the fraction from 145°C to 360°C. The unconverted bottoms fraction is considered to be any fraction above 360°C.

[0089] For the hydrocracking process, the pilot plant was loaded with 100 mL of the commercial pretreated catalyst and then 100 mL of catalyst composition 1 or catalyst composition 2. Hydrogen was introduced at a partial pressure of 13.5 MPa at a rate of 1000 Nm 3 / m 3 The hydrogen / oil ratio was added to the pilot plant. The reactions were carried out sequentially at 360°C, 375°C, 390°C and 405°C without cooling between increases.

[0090] Table 3 provides a measure of the catalytic activity, expressed as the temperature at which 50 wt.% conversion is observed, for Catalyst Composition 1 and Catalyst Composition 2. In addition, Table 3 provides the wt.% of various distillates obtained using each catalyst composition.

[0091] Table 3

[0092]

[0093] 1 Value of catalyst composition 1 - value of catalyst composition 2

[0094] The results show that when all other variables are significantly similar, Catalyst Composition 1, which includes 5 wt.% TiZr-β zeolite, achieves 50% conversion at a temperature 2.3°C lower than the temperature at which Catalyst Composition 2, which includes only TiZr-USY zeolite, achieves the same level of conversion. In addition, Catalyst Composition 1 produces 0.3 wt.% more C1-C4 gas and 1.5 wt.% more naphtha at the expense of middle distillates.

[0095] It should be noted that, in contrast to statements of intended use, statements in this disclosure that a component of the present disclosure is "operable" or "sufficient" in a particular manner to exhibit a particular property or function in a particular manner are structural statements. More specifically, references in this disclosure to the manner in which a component is "operable" or "sufficient" refer to the existing physical condition of the component and are therefore to be regarded as explicit statements of the structural characteristics of the component.

[0096] The subject matter of the present disclosure has been described in detail and by reference to specific embodiments, it should be noted that the various details disclosed in the present disclosure should not be considered to imply that these details relate to elements that are essential components of the various embodiments described in the present disclosure. In addition, it is apparent that modifications and variations are possible without departing from the scope of the present disclosure, including but not limited to the embodiments defined in the appended claims.

[0097] The singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.

[0098] Throughout this disclosure, ranges are provided. It is contemplated that each discrete value encompassed by the range is also included. Additionally, ranges that can be formed from each discrete value encompassed by the explicitly disclosed ranges are also contemplated.

[0099] As used in the present disclosure and appended claims, the words "comprise," "have," and "include" and all grammatical variations thereof are each intended to have an open, non-limiting meaning that does not exclude additional elements or steps.

[0100] As used in the present disclosure, terms such as "first" and "second" are arbitrarily assigned and are intended only to distinguish between two or more instances or components. It should be understood that the words "first" and "second" are not used for other purposes and are not part of the name or description of the components, nor do they necessarily define the relative position, location, or order of the components. In addition, it should be understood that the use of the terms "first" and "second" alone does not require the existence of any "third" component, although such a possibility is contemplated within the scope of the present disclosure.

Claims

1. A catalyst composition comprising: Catalyst carrier; as well as at least one hydrogenation metal component disposed on the catalyst support, Wherein, the catalyst carrier comprises: at least one ultrastable Y-type zeolite having a framework substituted with titanium and zirconium (TiZr-USY zeolite); and at least one beta zeolite having a framework substituted with titanium and zirconium (TiZr-beta zeolite); wherein the at least one TiZr-USY zeolite and the at least one TiZr-β zeolite are each independently substituted with 0.1 wt.% to 5 wt.% of zirconium atoms and 0.1 wt.% to 5 wt.% of titanium, calculated on an oxide basis.

2. The catalyst composition according to claim 1, wherein The at least one hydrogenation metal component is selected from the group consisting of chromium, molybdenum, tungsten, iron, cobalt, nickel, copper, ruthenium, rhodium, palladium, silver, osmium, iridium, platinum, gold, and combinations of two or more thereof.

3. The catalyst composition according to claim 1 or 2, wherein The at least one TiZr-USY zeolite comprises a lattice constant of 2.43 nm to 2.45 nm.

4. The catalyst composition according to claim 1 or 2, wherein The at least one TiZr-USY zeolite comprises a molar ratio of SiO2 to Al2O3 of 10 to 100.

5. The catalyst composition according to claim 1 or 2, wherein The at least one hydrogenation metal component comprises 0.01 wt. % to 40 wt. % of the catalyst composition.

6. The catalyst composition according to claim 1 or 2, wherein The catalyst support includes 70 wt.% to 99 wt.% of TiZr-USY zeolite, based on the total zeolite content of the support.

7. The catalyst composition according to claim 1 or 2, wherein The catalyst support includes 1 wt.% to 30 wt.% of TiZr-β zeolite, based on the total zeolite content of the support.

8. The catalyst composition according to claim 1 or 2, wherein The catalyst support includes 1 wt. % to 80 wt. % total TiZr-USY zeolite and TiZr-β zeolite.

9. A method for hydrocracking a hydrocarbon oil comprising: Contacting at least one hydrocarbon oil stream with at least one hydrocracking catalyst composition and hydrogen in a reactor to hydrocrack the hydrocarbon oil stream, the hydrocracking catalyst composition comprising: a catalyst support; and at least one hydrogenation metal component disposed on the catalyst support, Wherein, the catalyst carrier comprises: at least one ultrastable Y-type zeolite having a framework substituted with titanium and zirconium (TiZr-USY zeolite); and at least one beta zeolite having a framework substituted with titanium and zirconium (TiZr-beta zeolite); wherein the at least one TiZr-USY zeolite and the at least one TiZr-β zeolite are each independently substituted with 0.1 wt.% to 5 wt.% of zirconium atoms and 0.1 wt.% to 5 wt.% of titanium, calculated on an oxide basis.

10. The method according to claim 9, wherein: The reactor is operated at a temperature of 300°C to 500°C.

11. The method according to claim 9, wherein: The hydrocarbon oil has a boiling point of 375°C to 833°C.

12. The method according to claim 10 or 11, wherein: The hydrogen gas is added to the reactor at a pressure of 3.5 MPa to 35 MPa.

13. The method according to claim 10 or 11, wherein: The reactor has a 500 Nm 3 / m 3 Up to 2500Nm 3 / m 3 of hydrogen / oil ratio.

14. The method according to claim 10 or 11, wherein: The reactor has a liquid hourly space velocity of 0.1 / hour to 10 / hour.

Citation Information

Patent Citations

  • Hydrocracking catalyst for hydrocarbon oil, method for producing hydrocracking catalyst, and method for hydrocracking hydrocarbon oil with hydrocracking catalyst

    US10293332B2

  • HYDROCRACKING CATALYST COMPRISING A BETA ZEOLITE (*BEA) FRAMEWORK SUBSTITUTED WITH Ti AND Zr AND METHODS FOR ITS PREPARATION AND USE

    US20210095213A1

  • Hydrocracking catalyst containing beta and y zeolites, and process for its use to produce naphtha

    CN101300326A

  • Hydrocracking catalyst for hydrocarbon oil, method for producing hydrocracking catalyst, and method for hydrocracking hydrocarbon oil with hydrocracking catalyst

    CN103269795A